2003
DOI: 10.1046/j.1439-0531.2003.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Reproductive Efficiency, Pregnancy Diagnosis and Monitoring the Resumption of Luteal Activity in Indigenous Damascus Goats

Abstract: Seventy-five female Damascus goats aged between 1.5 and 5.5 years were used to evaluate the effectiveness of the intravaginal sponges and prostaglandin analogue on oestrous synchronization and fecundity; to diagnose pregnancy and to monitor the resumption of the luteal activity. Females were divided randomly, during the breeding season, into three equal groups, S, P and C. Females in group S were fitted with sponges containing 45 mg of flugestone acetate (FGA) for 14 days and injected with pregnant mare serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
4
6
0
Order By: Relevance
“…Such successful outcome using progestagen-eCG during the non-breeding season has been reported previously (Zarkawi et al 1999). Steroid hormones concentrations reported in this study are typical of those reported in goats in the anestrus period after estrus induction (Al-Merestani et al 2003). Progesterone profile in the control group is typical of those reported with short luteal phase (Al-Merestani et al 2003).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Such successful outcome using progestagen-eCG during the non-breeding season has been reported previously (Zarkawi et al 1999). Steroid hormones concentrations reported in this study are typical of those reported in goats in the anestrus period after estrus induction (Al-Merestani et al 2003). Progesterone profile in the control group is typical of those reported with short luteal phase (Al-Merestani et al 2003).…”
Section: Discussionsupporting
confidence: 84%
“…Steroid hormones concentrations reported in this study are typical of those reported in goats in the anestrus period after estrus induction (Al-Merestani et al 2003). Progesterone profile in the control group is typical of those reported with short luteal phase (Al-Merestani et al 2003). Abrupt introduction of bucks to goats in the transitional period to anestrus is usually followed by ovulation and development of a corpus luteum with short life span which fails prematurely about 4-to 6-day after ovulation (Chimineau 1987).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…1997;Motlomelo et al, 2002;Al-Merestani et al, 2003;Romano, 2004;Dogan et al, 2008), where FGA sponges, in period changed between 6-16 days, with combination of eCG and PGF 2α or both, were used in goats during the transition period or breeding season.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, previous studies reported a high level of estrus synchronization using a combination of progesterone and eCG in ewes [20] and goats [26,32]. A combination of progesterone and eCG has been used in ewes and goats during the non-breeding as well as breeding seasons [2,8, 15,18]. However, it has been suggested that long periods of progesterone treatment are associated with lower fertility [10,31].…”
Section: Introductionmentioning
confidence: 99%